Thinking flags method effects on pupil process skills and achievement in science - Bosi, Ellen Florita L. Sabado (2007)
The study was undertaken to determine the effects of the Thinking Flags Method (TFM) on pupil process skills and achievement in science. The research involved two intact classes with 32 pupils each in Buguey North Central Elementary Schools, Division of Cagayan. One section was exposed to TFM, while the other was taught using the traditional method of teaching by the same teacher. The study used the quasi-experimental two-group design. The Science Achievement Test and the Perez Test of Science Processes were both used to gather data for the research. It was found that there was greater improvement in the achievement mean posttest scores of students for the TFM group for poor to above average. Employing TFM significantly improved the science skills of the students in the TFM group.
Thesis (M.A. General Science Education)--University of the Phillipines, Diliman.
Keywords: Science -- Study and teaching (Elementary) -- Philippines -- Cagayan; School children -- Philippines -- Cagayan; Academic achievement -- Philippines -- Cagayan